Priorities for developing stroke care in Ireland from the perspectives of stroke survivors, family carers and professionals involved in stroke care: A mixed methods study. - Eithne Sexton; Karen Fowler; Anne Hickey; David J Williams; Frances Horgan; Elaine Byrne; Chris Macey; Padraic Cuffe; Suzanne Timmons; Kathleen Bennett (PLoS ONE, 2024)
Introduction Increasing numbers of people are living with stroke, due to population ageing and improved survival, leading to a need for evidence to inform future policy decision-making. This study aimed to engage with stakeholders in Ireland to identify priorities for stroke services development. Methods A sequential mixed methods design was used. Phase 1 (qualitative) was exploratory, involving initial priority gathering via an online qualitative survey and interviews, with stroke survivors, family/main carers, and professionals working in stroke care. Framework analysis was used to generate a long-list of improvements to stroke services. Phase 2 involved a quantitative survey, where stakeholders selected five priority improvements from the long-list. Results were discussed in a stakeholder meeting. Results In-depth interviews were completed with 18 survivors, 13 carers and 8 professionals, while 80 professionals took part in a qualitative survey (phase 1). Priority areas of care were identified and a long-list of 45 priority improvements was generated. In phase 2, 34 survivors, 19 family carers and 42 professionals completed a survey. The highest priority improvements (selected by >20% of respondents) were access to specialist neuro-rehabilitation, ongoing support for life after stroke, recruitment/retention of specialist staff, improved information and support for health system navigation, and access to specialist acute care. Stroke survivors/carers prioritised exploring ways to improve access for strokes with atypical presentation, while professionals prioritised specialist inpatient rehabilitation and early supported discharge. Neither group prioritised stroke prevention. Based on discussions in the stakeholder meeting (n = 12), it was decided that support for mental health should also be included as a priority. Discussion The development of stroke services benefits from exploring the priorities of those receiving and delivering stroke care. Findings emphasise the need for equitable access to high quality adequately-staffed services, particularly post-discharge, that are easy to navigate, with good communication, and effective information provision.